2014
DOI: 10.1080/00223980.2013.818929
|View full text |Cite
|
Sign up to set email alerts
|

Do You Put Your Best Foot Forward? Interactive Effects of Task Performance and Impression Management Tactics on Career Outcomes

Abstract: This study aims to investigate the interactive effects of task performance and impression management tactics on career outcomes from the socioanalytic perspective. Based on a survey of 195 employee-supervisor dyads from various industries in Taiwan, a hierarchical regression analysis revealed that (1) the relationship between task performance and a one-year salary adjustment was greater among employees who frequently employ ingratiation than among those who do not, (2) the relationship between task performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 57 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Career satisfaction is an important subjective career outcome, and it is shown to be the result of processes requiring agency in managing one's career, such as career self-management (King, 2004), impression management (Cheng et al, 2014), and career adaptability (Rudolph et al, 2017). For example, studying 195 employee-supervisor dyads from various industries in Taiwan, Cheng et al (2014) showed that individuals who employed self-promotion behaviors showed greater career satisfaction compared to those who did not employ such behaviors. Since personal branding and self-promotion are self-presentation behaviors, we hypothesized that personal branding would also be positively related to career satisfaction.…”
Section: Personal Branding and Career Outcomesmentioning
confidence: 99%
“…Career satisfaction is an important subjective career outcome, and it is shown to be the result of processes requiring agency in managing one's career, such as career self-management (King, 2004), impression management (Cheng et al, 2014), and career adaptability (Rudolph et al, 2017). For example, studying 195 employee-supervisor dyads from various industries in Taiwan, Cheng et al (2014) showed that individuals who employed self-promotion behaviors showed greater career satisfaction compared to those who did not employ such behaviors. Since personal branding and self-promotion are self-presentation behaviors, we hypothesized that personal branding would also be positively related to career satisfaction.…”
Section: Personal Branding and Career Outcomesmentioning
confidence: 99%
“…We also consider the interaction effects of different IM tactics. The majority of individual-level IM empirical research has examined IM tactics in isolation (e.g., Yun et al, 2007; Cheng et al, 2014), and seldom considered the use of different combinations of IM. However, IM tactics likely interact with each other (Bolino et al, 2008, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Second, error disclosure damages error makers' image on job competence, attitudes or involvement (Dyck et al, 2005;Gronewold et al, 2013;Uribe et al, 2002). Employee image is a job resource because it facilitates the employee's performance and development in the organization (Cheng et al, 2014). Hence, employees will be reluctant to share, i.e.…”
Section: Errors and Error Disclosure At Workmentioning
confidence: 99%
“…Error disclosure damages employee images on job competence, attitudes or involvement (Dyck et al, 2005;Gronewold et al, 2013;Uribe et al, 2002). Since workplace image facilitates job continuance and development and is an important job resource (Cheng et al, 2014), error disclosure induces a loss of image resource. The personal cost of error disclosure is that error disclosure consumes both time and energy resources at work, both of which are required to report and explain errors (Dyck et al, 2005;Gronewold et al, 2013;Uribe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%